Prolyl hydroxylase domain enzyme PHD2 inhibits proliferation and metabolism in non-small cell lung cancer cells in HIF-dependent and HIF-independent manners - Deng, Hongyan; Wang, Zixuan; Zhu, Chunchun; Chen, Zhu (Frontiers in Oncology, 2024)
Prolyl hydroxylase domain protein 2 (PHD2) is one of the intracellular oxygen sensors that mediates proteasomal degradation of hypoxia-inducible factor (HIF)-α via hydroxylation under normoxic conditions.Because of its canonical function in the hypoxia signaling pathway, PHD2 is generally regarded as a tumor suppressor. However, the effects of PHD2 in tumorigenesis are not entirely dependent on HIF-α. Based on analysis of data from the Cancer Genome Atlas (TCGA) database, we observed that the expression of PHD2 is upregulated in non-small cell lung cancer (NSCLC), which accounts for approximately 80-85% of lung cancers. This suggests that PHD2 may play an important role in NSCLC. However, the function of PHD2 in NSCLC remains largely unknown. In this study, we established PHD2-deficient H1299 cells and PHD2knockdown A549 cells to investigate the function of PHD2 in NSCLC and found that PHD2 suppresses cell proliferation and metabolism but induces ROS levels in human NSCLC cells. Further results indicated that the function of PHD2 in NSCLC is dependent on its enzymatic activity and partially independent of HIF.Moreover, we performed RNA-sequencing and transcriptomic analysis to explore the underlying mechanisms and identified some potential targets and pathways regulated by PHD2, apart from the canonical HIFmediated hypoxia signaling pathway. These results provide some clues to uncover novel roles of PHD2 in lung cancer progression.